Textiloma Mimicking Superior Sulcus Tumor: Positron Emission Tomography/Computed Tomography Findings of a Pseudotumor - Fındıkcıoğlu, Alper; Karadayi, Sule; Kilic, Dalokay; Hatipoglu, Ahmet (The Thoracic and Cardiovascular Surgeon, 2014)
We present an interesting case report of a 52-year-old man with a superior sulcus tumor. To evaluate the suspicious left lung tumor, 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) was used. Increased FDG level was indicative of a malignant tumor. Left thoracotomy revealed a textiloma retained during cardiac surgery.
Keywords: positron emission tomography; PET; tumor; lung cancer; diagnosis